Denitrification in the Antarctic stratosphere - Salawitch, R. J.; Gobbi, G. P.; Wofsy, S. C.; Mcelroy, M. B. (1989)
Rapid loss of ozone over Antarctica in spring requires that the abundance of gaseous nitric acid be very low. Precipitation of particulate nitric acid has been assumed to occur in association with large ice crystals, requiring significant removal of H2O and temperatures well below the frost point. However, stratospheric clouds exhibit a bimodal size distribution in the Antarctic atmosphere, with most of the nitrate concentrated in particles with radii of 1 micron or greater. It is argued here that the bimodal size distribution sets the stage for efficient denitrification, with nitrate particles either falling on their own or serving as nuclei for the condensation of ice. Denitrification can therefore occur without significant dehydration, and it is unnecessary for temperatures to drop significantly below the frost point.